Sub-100-nm negative bend resistance ballistic sensors for high spatial resolution magnetic field detection - Gilbertson, A. M. (American Institute of Physics, 2011)
We report the magnetic field detection properties of ballistic sensors utilizing the negative bend resistance of InSb∕In(1−x)Al(x)Sb quantum well cross junctions as a function of temperature and geometric size. We demonstrate that the maximum responsivity to magnetic field and its linearity increase as the critical device dimension is reduced. This observation deviates from the predictions of the classical billiard ball model unless significant diffuse boundary scattering is included. The smallest device studied has an active sensor area of 35×35 nm(2), with a maximum responsivity of 20 kΩ∕T, and a noise-equivalent field of [Formula: see text] at 100 K.